OVeRS: Online Venue Reservation System for university facilities - Olanrewaju, Rashidah Funke; Ajayi, Binyamin Adeniyi; Zakaria, Amer Fathullah N. (Nigeria Computer Society, 2022)
Online reservation system can store data and information that can benefit the end-user, such as booking for halls, or venue reservations for weddings and other events. Such systems when available give convenience and optimal usage. However, the available way for booking venues in a case university’s faculty, for purposes other than class or lecture time is through the manual process usually at the Dean’s Office. This study developed an integrated web and mobile app for online venue reservations without the need for physical application at the office. The system is designed to have all the information about the venues in the faculty. Using the technology of hybrid framework, by integrating the Web and Mobile APP, the system was developed using a single code. Thus, without the need to program separate code for different platforms or operating systems, OVeRS was developed. The system’s client side was developed using Ionic for both the web and mobile apps. For the server side, Firebase was used where the database, web hosting, and user authentication are automatically configured by the Firebase’s rich functionalities. Using the database as the center of the system, the web and mobile app can communicate with each other.